Modeling Shariah business screening for compliance in Islamic finance / Noor Latiffah Adam - Adam, Noor Latiffah (2022)
This research explores one of the important issues in Islamic finance, which is Shariah compliant status - a level of acceptance of certain situations or events according to the Islamic faith. In order to determine Shariah-compliant status for products or services of a company, it must go through a series of tedious checks and testing before a Shariah advisory committee puts it on the compliance list. This work focuses on Shariah-compliant status of a company’s core business. The screening for Shariah compliant begins with information extraction. Islamic finance has grown exponentially. In returns, it has huge data in the form of notes, descriptions, numbers, and transactions available on the web. Based on this argument, it is not easy to find the connection between one information to another when you have more than one million hits every time you search for some keywords. In order to get information about the company’s core business, we reduced the search scope to only the corporate website of that company. The corporate websites of selected companies were crawled and extracted. After some cleaning process, the outcome was found to be adequate to be used as the data sources for screening. Next, the data sources are compared with a list of keywords, known as the screening criteria that have been tabulated from the literature. A negative screening approach was adopted, where, if none of the prohibited elements exist in the company’s core business, then it will be deemed as Shariah-compliant, otherwise, it is Shariah non-compliant. The screening process consists of repetitive action. It happens because the company may have multiple core businesses. In this work, we have represented the repetitive actions through a Business Screen State Model. The Business Screen State Model could serve as a general model for automatic screening processes. In addition to that, Business Screening Model was formulated using the screening criteria. The Business Screening Model could be used to provide rules for Shariah classification. The screening criteria can also be embedded into analytic tools for Shariah screening for compliance. Finally, we were able to construct Shariah Business Screening Ontology using a task ontology approach. We illustrate the ontology using structural and behavioral models made of UML class diagram and activity diagram. This ontology represents the knowledge roles and control-flow of the screening process. It can be part of any suitable Shariah screening application.